Dandysme ou le goût de la provocation - Kociubińska, Edyta (Romanica Silesiana)
The present paper is concerned with the most important figures and forms of dandyism in the XIX century. It also outlines the main characteristics of the phenomenon, as well as reflects on a number of literary dandies. According to Barbey d’Aurevilly, dandyism is as difficult to describe as it is to define. In his essay “Mon cœur mis à nu” Charles Baudelaire commented that dandies had “no profession other than elegance […] no other status but that of cultivating the idea of beauty in their own persons. The dandy must aspire to be sublime without interruption; he must live and sleep before a mirror”. In fact, the magic of dandyism resides in the permanent interplay between the dandy’s temperament and his appearance. Key words: Dandyism, esthetisme, provocation, Charles Baudelaire, Barbey d’Aurevilly.